Kepuasan Berkunjung Taman Impian Jaya Ancol yang Dipengaruh Lifestyle, Persepsi Harga, dan Daya Tarik Wisata - Hairani Tarigan (CV. Ulil Albab Corp, 2024)
This study investigates the impact of lifestyle, price perceptions, and tourist attractions on visitor satisfaction at Taman Impian Jaya Ancol Jakarta. Data was collected in January 2023 from 100 respondents visiting Taman Impian Jaya Ancol. Of these, 20 respondents were used to test the validity and reliability. In comparison, the other 80 respondents were used for the multiple linear regression test to identify the effect simultaneously or partially. Sampling was conducted using the Roscoe technique, about 15-20 times the number of existing variables. The results of this study concluded several important things. Overall, the three independent variables, lifestyle, price perceptions, and tourist attractiveness, significantly influence the satisfaction level of visiting. Partially, lifestyle significantly influences the level of visit satisfaction; perceived price also influences visit satisfaction, while tourist attraction does not significantly impact visitor satisfaction.